EFEITO DA SUPLEMENTAÇÃO COM AMINOÁCIDOS SOBRE O METABOLISMO DE EQUINOS - Uriel de Almeida Curcio (2025)
The objective of this study was to evaluate the effect of amino acid and mineral supplementation in a molasses-based supplement on the energy and protein metabolism of horses. The experimental design was a crossover with 2 treatments, 6 animals and two experimental periods. The treatments consisted of supplementation with 30 mL per 100 kg/BW of a molasses-based supplement with amino acids, vitamins and minerals or liquid sugarcane molasses. Six male, castrated Pantaneiro horses with an average weight of 395 ± 41 kg and age of 10 ± 4 years were used. The animals were also fed 0.5 kg DM/100 kg BW of commercial concentrate and 1.2 kg DM/100 kg BW of hay. Collections for blood gas analysis, blood biochemistry, fecal production, fecal pH, consumption rate and urine volume were performed in two periods of 20 days. There was no significant effect (P>0.05) for glucose, pH, bicarbonate, Ca²⁺, Na⁺, Cl⁻, K⁺, AST, GGT, ALT, creatinine, urea, total protein, albumin, globulin, albumin x globulin ratio, consumption rate, fecal production and urine volume in relation to the treatments studied. There was a treatment effect for lactate (P=0.0242) and fecal pH (P=0.0286). Lactate concentrations were higher in the molasses treatment compared to the supplement (0.90 ± 0.05 x 0.79 ± 0.05) and fecal pH was lower in the supplement treatment compared to molasses (5.77 ± 0.13 x 6.04 ± 0.13). Supplementation with amino acids, vitamins and minerals does not alter the protein metabolism of animals, nor glycemia and electrolytes, but it altered fermentation in horses.